1995
DOI: 10.1002/jbm.820291102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on the degradation of reinforcing fibers for absorbable implants

Abstract: Calcium phosphate fibers designed for reinforcement of bioabsorbable fracture fixation devices were evaluated for their properties upon annealing. The composition of these fibers were 54% PO4, 27% Ca, 12% ZnO, 2.5% NaPO3, and 4.5% Fe2O3, and they were either not annealed, annealed at 250 degrees C, or annealed at 420 degrees C. Chemical degradation, mass loss, and morphology upon degradation were studied. Chemical degradation was performed in Tris-buffered HCl, while mass loss and morphologic studies were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 18 publications
9
44
1
Order By: Relevance
“…Other authors in the literature investigated the influence of a heat treatment on the dissolution of phosphate glass fibres, and found similar results [38][39][40]. Choueka et al [38] studied the influence of heat treatments on the dissolution of phosphate glass fibres containing zinc and iron. The authors observed that the degradation rates for the fibres were inversely proportional to the annealing temperature.…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 74%
See 2 more Smart Citations
“…Other authors in the literature investigated the influence of a heat treatment on the dissolution of phosphate glass fibres, and found similar results [38][39][40]. Choueka et al [38] studied the influence of heat treatments on the dissolution of phosphate glass fibres containing zinc and iron. The authors observed that the degradation rates for the fibres were inversely proportional to the annealing temperature.…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 74%
“…Numerous studies in the literature describe a loss of structural integrity of the phosphate glass fibres during dissolution [7,[38][39][40]42,43]. Cozien-Cazuc et al [39,40] observed the formation of an outer hydrated layer and delamination during dissolution on both as-drawn and annealed glass fibres with composition 40P 2 O 5 -20Na 2 O-16CaO-24MgO (mol.%).…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation rates are influenced by processing routes, such that thermally annealed glasses degrade at slower rates compared to their melt quenched counterparts 47,[52][53] . Magnetron sputtering produces instantaneously quenched coatings upon a substrate, forming residual tensile stresses within the atomic layers, which may therefore account for higher degradation rates within the glass.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetron sputtering produces instantaneously quenched coatings upon a substrate, forming residual tensile stresses within the atomic layers, which may therefore account for higher degradation rates within the glass. Cozien-Cazuc et al showed annealing at 5 °C below the Tg for fibres, allowing the structure to reorientate to its more thermodynamically stable position and relieving internal stresses reduced dissolution by half [52][53] .…”
Section: Discussionmentioning
confidence: 99%